Methodological Characteristics of Clinical Trials Supporting the Marketing Authorisation of Advanced Therapies in the European Union - Iglesias-Lopez, Carolina; Agustí, Antònia; Vallano, Antonio; Obach, Merce (Frontiers in Pharmacology, 2021)
Several advanced therapy medicinal products (ATMPs) have been approved in the European Union (EU). The aim of this study is to analyse the methodological characteristics of the clinical trials (CT) that supported the marketing authorization (MA) of the approved ATMPs in the EU. A systematic review of the characteristics of pivotal CT of ATMPs approved in the EU until January 31st, 2021 was carried out. A total of 17 ATMPs were approved and 23 CT were conducted to support the MA (median, 1, range, 1 to 3). Of those studies, 8 (34.78%) were non-controlled and 7 (30.43%) used historical controls. Only 7 (30.4%) were placebo or active-controlled studies. Among all CT, 21 (91.3%) were open-label and 13 (56.52%) had a single-arm design. To evaluate the primary endpoint, 18 (78.26%) studies used an intermediate and single variable. The median (IQR) number of patients enrolled in the studies was 75 (22-118). To date, ATMPs’ approval in EU is mainly supported by uncontrolled, single-arm pivotal CTs. Although there is a trend toward an adaptive or a life cycle approach, a switch to more robust clinical trial designs is expected to better define the benefit and the therapeutic added value of ATMPs.